Currents, waves and sediment transport around the headland of Pt. Dume, California. (1st December 2018) - George, Douglas A.; Largier, John L.; Storlazzi, Curt D.; Robart, Matthew J.; Gaylord, Brian
Abstract: Sediment transport past rocky headlands has received less attention compared to transport along beaches. Here we explore, in a field-based study, possible pathways for sediment movement adjacent to Point Dume, a headland in Santa Monica Bay, California. This prominent shoreline feature is a nearly symmetrical, triangular-shaped promontory interior to the Santa Monica Littoral Cell. We collected current, wave, and turbidity data for 74 days during which several wave events occurred, including one associated with a remote hurricane and another generated by the first winter storm of 2014. We also acquired sediment samples to quantify seabed grain-size distributions. Near-bottom currents towards the headland dominated on both of its sides and wave-driven longshore currents in the surf zone were faster on the exposed side. Bed shear stresses were generated mostly by waves with minor contributions from currents, but both wave-driven and other currents contributed to sediment flux. On the wave-exposed west side of the headland, suspended sediment concentrations correlated with bed stress suggesting local resuspension whereas turbidity levels on the sheltered east side of the headland are more easily explained by advective delivery. Most of the suspended sediment appears to be exported offshore due to flow separation at the apex of the headland but may not move far given that sediment fluxes at moorings offshore of the apex were small. Further, wave-driven sediment flux in the surf zone is unlikely to pass the headland due to the discontinuity in wave forcing that causes longshore transport in different directions on each side of the headland. It is thus unlikely that sand is transported past the headland (specifically in a westerly direction), although some transport of finer fractions may occur offshore in deep water. These findings of minimal sediment flux past Point Dume are consistent with its role as a littoral cell boundary, although more complex multi-stage processes and unusual events may account for some transport at times. Highlights: Currents, waves, and sediment transport were measured around a prominent headland. Currents over 74 days were apex-ward on each side and reversing at the point. Sand and mud transport are likely decoupled with sand ejected offshore. Two flow separation regimes are proposed from current patterns around the point. The headland is a likely littoral cell boundary for some sediment fractions.